Synthesis, characterization and liquid crystalline properties of organometallic complexes of chromium, cobalt and platinum - Starr, Earl Jeffrey (Department of Chemistry, 2016)
Chapter 1 provides a concise review of concepts and previous studies in liquid crystal chemistry as they relate to metallomesogens, highlighting their advantages over purely organic liquid crystal systems. Chapter 2 reports on a mild synthetic route starting from [Co(DH)₂(py){(CH₂)ₘOH}] (DH = the monoanion of dimethylglyoxime; py = pyridine; m = 3 or 8) to give the ester-functionalized cobaloximes [Co(DH)₂(py){(CH₂)ₘOC(O)(CH₂)ₙC₆H₄R}] (n = 0, 2 or 5; R = H, o-, m-, p-OCH₃, p-OC₇H₁₅ or p-OC₉H₁₉), 1- 9. The esterification occurred chemoselectively to extend the hydroxy alkyl group, without affecting the oxime entities on the DH ligands. None of these complexes displayed mesogenic properties. This chapter also details the synthesis and characterization of the new complexes [Co(DH)₂(C₆H₄₀CₘH₂ₘ₊₁)(n-OST)] (m = 8, 10 or 12; n-OST = trans-4-n-alkoxy-4'stilbazole; n = 8, 10 or 12), 11 - 17, which possess greater structural anisotropy and consequently displayed an enantiotropic smectic C mesophase. The extended rod-like core and the central position of the bulky metal system proved useful in promoting the formation of the mesophase. Variation of the above cobaloxime-stilbazole system afforded the complexes [Co(DH)iC₆H₄₀C₁₂H₂₅)(R-OST)] 18, [Co(DH)₂(C₁₄H₂₉)(12- OST)] 19, and [Co(DH)₂(C₁₄H₂₉)(R-OST)] 20 (where R = C(O)C₆H₄₀C₉H₁₉). These complexes were non-mesomorphic, despite possessing favourable rod-like structures. The synthesis and characterization of the novel octahedral stilbazole complexes [PtMe₂X₂(n-OST)₂] (X= I or Br; n = 3 - 10 or 12), 21- 30, is described in Chapter 3. The shorter-chain homologues melted cleanly to the isotropic state while the complexes with n = 8 - 10 or 12 developed an unusual pseudo-isotropic phase around 80 °C and on further heating, the samples displayed a smectic C phase around 150 °C. The alignment of the molecules to give the mesophase occurred despite the fact that the complexes possessed an angular structure resulting from the cis geometry of the n-OST ligands. The complexes [PtMe₂RX(n-Diim)], [PtMe₂X₂(8-Diim)] and [ {PtMe₂Br(9- Diim)}₂(μ-p-(CH₂)₂C₆H₄)] (R =Me, Et, n-Pr; X= I or Br; n-Diim = N,N'-bis-4'-(4-nalkoxybenzoyloxyphenyl)- 1,4-diaza-1,3-butadiene), 31- 42, were synthesized in a one- pot procedure from the dimeric complex [Pt₂Me₄(μ-SMe₂)₂] and the respective n-Diim ligand to give the square-planar intermediate [PtMe₂(n-Diim)], which underwent subsequent oxidative addition in the presence of an alkyl halide RX (R = Me, Et, n-Pr) or a dihalide X₂ (X = Br or I). An aromatic-like metallocyclic ring was proposed to explain the anomaly in the NMR resonances of the protons close to the coordination sphere in the square-planar complexes. The longer-chain complexes (i.e. n = 6 - 10) exhibited wide temperature-range enantiotropic nematic phases. Further, modification of the axial ligands to increase the bulkiness of the central metal core (R = Me to n-Pr, X = Br or I) generally led to lower-melting materials. However, many of the complexes were thermally unstable, decomposing at their clearing temperatures. Chapter 4 describes the synthesis and characterization of the novel ionic complexes Y[PtC₁₃(olefin)] (where Y = K, H₂₁C₁₀NH₃, NMe₄, NEt₄ and olefin = CH₂=CHC₆H₄- C(O)OC₆H₄₀R, R = C₇H₁₅ , C(O)C₆H₄₀CH₃ or C(O)C₆H₄₀C₈H₁₇), 43 - 50. By careful choice of the reaction conditions and work-up solvents, most of the individual reaction steps produced high yields of the desired products. The meso genic behaviour was found to be dependent on the length of the rod-like core, the length of the flanking alkoxy chain, and more importantly, the nature of the cation used. Only the long-chain alkylammonium complexes displayed stable nematic phases. Variation of the now established mesogemc platinum(II)-olefin system afforded the complexes [PtC₁₂(olefin)(N-donor)] (N-donor = 4,4'-bipy, H₂NC₄H₉, H₂NC₁₀H₂₁ or 4-0ST), 51- 54. Except for the 4,4'-bipy complex 51 which was non-mesomorphic, the remaining complexes displayed well-formed nematic phases. The greater structural anisotropy of the stilbazole complex 54 produced a mesophase with a wider temperature range than that observed for the alkylamine complexes. Finally, Chapter 5 reports on a simple one-pot synthesis leading to the new complexes [ {η⁶-C₆H₄R₂-1,4}Cr(CO)₃] (where R = OC(O)C₆H₄₀CnH₂n+l (n = 1, 6 - 10) or OC(O)C₆H₄C₅H₁₁ ) and [ {η⁶-C₆H₄(R')(C₆H₄R')-1,4 }Cr(CO)₃] (R' = OC(O)C₆H₄₀C₁₀H₂₁), 55 - 62. The procedure involved thermal reaction of Cr(CO)₆ with hydroquinone and subsequent esterification of the para hydroxyl functionalities with various mesogenic carboxylic acid compounds. Infrared monitoring of the reaction mixture provided useful data in identifying the reaction intermediates. Despite the bulky nature of the central chromium system, the rigid unit comprising three aromatic rings proved sufficient to stabilize enantioptropic nematic phases similar to those observed for the metal-free analogues. Modification of the organic backbone in these complexes to incorporate cyclohexylene rings and the biphenylene unit had pronounced effects on the temperature range of the observed mesophase.